Mobile Performance – Example of Website Performance Testing - Karol KROL (Communications of International Proceedings, 2021)
The performance of websites and web applications matters, particularly on mobile devices. The paper presents an experiment consisting of a snapshot measurement of the performance of a website prototype in desktop and mobile modes. The snapshot performance test means that values of selected aggregate indices were measured at a specific moment (a single measurement). The conclusion is that results of such (ad-hoc) measurements can be useful for a quick (overview) diagnosis of a website's or web application’s performance. Note that results of performance measurements in the form of aggregate indices can be unreliable or inaccurate.
Keywords: Mobile Performance; Aggregate Indices; Website Quality; User Experience; Usability; Performance Tests.